Fluidisation Enhancement Of Swirling Fluidised Bed Dryer With Distributor And Plenumchamber Modification - R.Goutham, Mufeed V E, (International Journal of Scientific Research and Management (IJSRM), 2016)
The hydrodynamic properties and mixing pattern in gas -solid fluidized beds are dependent on many parameters, such as gas properties, solid properties, gas entrance conditions, and distributor geometry. The fluidized bed is seen as a mass oscillating on top of an air-filled cavity called plenum chamber..  The swirling fliudised bed dryer plenum chamber  section  plays  a  vital  role  in  distributing  the  fluid  before  it  enters  the  distributor. The quality of distribution affects the  performance  of  the  fluidized  bed.Most researchers who investigate the hydrodynamics of fluidized beds did not take the effect of the plenum into account. Here fluidization enhancement of a swirling fluidized bed dryer with plenum chamber and distributor plate is taken into account and remodification is done.